Translating Educational and Cultural Literacy Works under Berne, Ius Cogens, and Linguistic Genocide - Klaus D Beiter (Potchefstroom Electronic Law Journal, 2024)
The lack of works for educational and cultural literacy purposes in their own languages threatens the cultural survival of many vulnerable minority and indigenous groups worldwide. Translation could satisfy related access needs. A strict reading of international copyright law, however, does not facilitate the translation of works into other languages. Yet, it is often forgotten that, in accordance with the integration rule of treaty interpretation, the Berne Convention, and other relevant international intellectual property instruments, would have to be read in the light of internationally protected linguistic human rights in education and for cultural literacy. This mechanism could go some way towards assisting the easier translation of (parts of) works for the stated purposes into other languages. The argument made in this article, however, is that a harmonious reading of existing international copyright law with international human rights law cannot go as far as to sufficiently resolve the access needs of vulnerable groups speaking an endangered language, insofar as translated texts are concerned. In fact, it is contended that the existing regulation of translation under international copyright law is so inimical to the survival of vulnerable groups and their languages that it must be held to promote cultural or linguistic genocide. For that reason, the relevant copyright rules must be considered to conflict with ius cogens, that is, peremptory norms of international law, and to be void in their application to neglected languages. The article makes suggestions as to how countries could design national copyright law regulating translation rights and limitations and exceptions in a way that facilitates translation generally, and into neglected languages specifically. These suggestions are based on a reappraisal of the true character of translation, which must be seen to be highly transformative in nature and resulting in the creation of autonomous new works.